Changes of Infant- and Family-Centered Care Practices Administered to Extremely Preterm Infants During Implementation of the NIDCAP Program - Klein, Valérie; Zores-Koenig, Claire; Dillenseger, Laurence; Langlet, Claire; Escande, Benoît; Astruc, Dominique; Le Ray, Isabelle; Kuhn, Pierre; , Strasbourg NIDCAP Study group (Frontiers in Pediatrics, 2021)
Introduction: Many studies have evaluated the Neonatal Individualized Developmental Care and Assessment Program (NIDCAP), but few studies have assessed changes in infant- and family-centred developmental care (IFCDC) practices during its implementation. Objectives: The primary objective of this single centre study was to investigate the impact of the implementation of the NIDCAP program on IFCDC practices used for management of extremely preterm infants (EPIs). The secondary objective was to determine during implementation the impact of this program on the short-term medical outcomes of all EPIs hospitalized at our centre. Methods: All EPIs (<28 weeks gestational age) who were hospitalized at Strasbourg University Hospital from 2007 to 2014 were initially included. Outborn infants were excluded. The data of EPIs were compared for three time periods: 2007 to 2008 (pre-NIDCAP), 2010 to 2011, and 2013 to 2014 (during-NIDCAP implementation) using appropriate statistical tests. The clinical and caring procedures used during the first 14 days of life were analysed, with a focus on components of individualized developmental care (NIDCAP observations), infant pain management (number of painful procedures, clinical pain assessment), skin-to-skin contact (SSC; frequency, day of initiation, and duration), and family access and involvement in the care of their children (duration of parental presence, parental participation in care). The short-term mortality and morbidity at discharge were evaluated. Results: We examined 228 EPIs who received care during the three time periods. Over time, painful procedures decreased, but pain evaluations, parental involvement in care, individualized observations, and SSC increased (all p < 0.01). In addition, the first SSC was performed earlier (p = 0.03) and lasted longer (p < 0.01). There were no differences in mortality and morbidity, but there were reductions in the duration of mechanical ventilation (p = 0.02) and the time from birth to first extubation (p = 0.02), and an increase of weight gain at discharge (p = 0.02). Conclusion: NIDCAP implementation was accompanied by progressive, measurable, and significant changes in IFCDC strategies. There were, concomitantly, moderate but statistically significant improvements in multiple important outcome measures of all hospitalised EPI.